Academic Entrepreneurship in Higher Education: A Scoping Study - Fayda-Kinik, F. Sehkar (Mokslines leidybos deimantas, MB, 2024)
Academic entrepreneurship (AE) in higher education institutions (HEIs) has a significant function in driving innovation and fostering economic development. By bridging the gap between academia and the business world, AE research advances theoretical understanding and offers practical implications for economic development through innovation, new venture creation, and enhanced regional and national economic performance. Therefore, this study aims to explore the landscape of AE research conducted in HEIs indexed in the Web of Science (WOS) in the past decade. A scoping review was performed on the eligible publications between 2013 and 2023 to explore the characteristics of AE research in HEIs. Of the 77 documents obtained at the initial screening, 21 articles on AE in HEIs were included in the review after the inclusion criteria were applied to the selected documents. These studies were evaluated in terms of publication year, WOS category, country, research focus, methodologies, outcomes, and implications. Based on the results, AE studies reached a peak in 2020 and the highest number of records were identified in the categories of Business and Management. Iran, Italy, China, Sweden, and the USA were the leading countries contributing significantly to the AE studies with various methodologies on diverse focuses. The prominent areas were detected as the success of AE initiatives, faculty performance, institutional support mechanisms, motivational factors, student/faculty experiences, organizational learning, and AE dynamics in the research outcomes and implications.